Effect of pretreatment on the enzymatic synthesis of rosin acid starch. (1st February 2016) - Li, He; Lin, Rihui; He, Junbin; Long, Han; Liao, Wei; Chen, Qiyong
Abstract : Esterification reaction efficiency was improved by pretreatment of starch, and the high DS of RAS was achieved. Abstract : A new esterified starch, rosin acid starch (RAS), had been synthesized under mild conditions, using rosin as a starting material directly with Novozym 435 as a catalyst. In order to improve the efficiency of the enzymatic reaction, native cassava starch (NCS) was pretreated by heat-moisture, ultrasonic, gelatinized, microwave and alkali before the enzymatic esterification. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis showed that the morphology and crystallinity of the NCS were changed according to the pretreated methods. Compared with NCS, the surface of ultrasonic and heat-moisture pretreated starch (PS) maintained a smooth and circular morphology structure, and the PS remained highly crystalline. The surface of alkali, microwave and gelatinized PS was changed from smooth to crude, with reducing crystalline, but they maintained some kinds of granule shapes. The activated effect of pretreatment on the degree of substitution (DS) of RAS was as follows: alkali RAS (0.0808) > microwave RAS (0.0174) > gelatinized RAS (0.0153) > ultrasonic RAS (0.0099) > heat-moisture RAS (0.0073) > native RAS (0.0053). The esterified products from PS were confirmed by FT-IR spectroscopy and nuclear magnetic resonance (NMR) analysis.